Source identification and apportionment of soil cadmium in cropland of Eastern China: a combined approach of models and geographic information system - Zhi, Yuyou; Li, Peng; Shi, Jiachun; Zeng, Lingzao; Wu, Laosheng (Journal of soils and sediments, 2016)
PURPOSE: Cadmium (Cd) is regarded as one of the most toxic heavy metals in the environment and can undermine the ecosystem function and human health at trace level due to its high toxicity. In order to reduce the anthropogenic Cd input into agricultural soil, it is of utmost importance to pinpoint the sources of Cd in soils and apportion their respective contributions. MATERIALS AND METHODS: One hundred twenty-seven topsoil samples and 21 subsoil samples were collected from croplands of Meishan Basin, Changxing County, Zhejiang Province, Eastern China, and analyzed for concentrations of Cd and other heavy metals. Finite mixture distribution model (FMDM) was employed to fit the data to obtain the local soil Cd threshold value, a critical indicator to assess soil heavy metal contamination. Then, principal component analysis (PCA) and geographic information system (GIS) were used to identify the potential sources of Cd. Finally, positive matrix factorization (PMF) was applied to apportion the source contributions. RESULTS AND DISCUSSION: Among the 127 topsoil samples, 71 were subject to Cd contamination with a mean concentration of 0.66 mg kg⁻¹ while the others were considered as background with a lower mean concentration of 0.145 mg kg⁻¹, close to the local background concentration of 0.142 mg kg⁻¹. Further, three components were extracted by PCA and interpreted as natural background, lead-acid battery manufacturing plants, and construction material associated activities, respectively. Additionally, most of the topsoil samples around the lead-acid battery manufacturing plants, construction material plants, and limestone/marble quarries were classified as Cd contaminated. However, PMF failed to get a successful portioning. CONCLUSIONS: Lead-acid battery manufacturing plants and construction material associated activities were the main anthropogenic sources of soil Cd contamination. With the help of FMDM, it is possible to distinguish the contaminated soil and estimate the contribution of anthropogenic sources to soil Cd. The apportionment by PMF was not successful in this paper due to the high skewness or outliers of Cd concentration in sampling sites and violation of the assumption that all samples have the same sources.